Manajemen Sumber Daya Pendidik Dan Tenaga Kependidikan Di Fakultas Keguruan Dan Ilmu Pendidikan Universitas Widya Gama Mahakam Samarinda - Ratnawati; Elis Nuryani; Odollar Sihombing; Azainil; Yudo Dwiyono; Agus Salim; Mahkamah Brantasari (AMMA : Jurnal Pengabdian Masyarakat, 2023)
Data collection methods use interviews, observation and documentation. The collected data was analyzed interactively to describe the situation and management process of educators and education personnel carried out by FKIP UWGM Samarinda. The implementation of human and academic resource management is carried out by integrating all elements of leadership and work units. There is the application of direct experience that supports management which is carried out both from planning, organizing, implementing, monitoring and evaluating. The management functions and duties of educators and education staff have implications for FKIP UWGM in dealing with the shortage of educators and education staff through placement. Coaching and development is also carried out for educators and education staff through training and further studies, which are carried out by study programs in every faculty at the University.